Gerakan Penyuluhan Penggunaan Pestisida Pada Kelompok Wanita Tani (KWT) Garuda Di Cipayung Ciputat - Cinta Rahmi; Aep Saefullah; Syarif Hidayatullah; Rasmawati AR; Adhy Firdaus; Joned Ceilandra Saksana; Muhammad Arief Noor; Hilda Fariha; Nur Aisyah; Nabila Akmas; Ibah Misbah (BADAN PENERBIT STIEPARI PRESS, 2021)
Pests and plant diseases cause suboptimal growth and development of plants. Usually, the cause of plants not growing and developing optimally is due to pests and diseases that attack and disrupt the plant system. Many farmers still depend on chemical pesticides to control pests and diseases. Besides being expensive, chemical pesticides also have many adverse effects on the environment and human health. Often, plants do not bear fruit, and only the leaves grow thicker. To address this issue, Cinta Rahmi from STIE Ganesha Jakarta conducted counseling on the use of natural pesticides made from citronella for the Women's Farmer Group Garuda in Cipayung Ciputat. The counseling method includes water control, leaf reduction, use of manure, sunlight care, and cleanliness of the plant area. This counseling is expected to reduce farmers' dependence on chemical pesticides and increase environmentally friendly crop yields.